Internalisasi Nilai Moral dengan Pendekatan Hadits Pendek di Madin Al Ulya Tretes Pasuruan - Ahmad Za'imul Umam; Abdulloh Hamid (Ta'allum: Jurnal Pendidikan Islam, 2020)
Hadith are the most important source of law and guidance for Muslims after the Qur'an. As a guide to life, certainly the hadith is very closely related to humans behavior. The excess value exept being a source of law and guidelines for life, we can get a lot of moral values contained therein also. One institution that implements moral education with hadith learning is madin al-ulya, an institution that located in the area of ​​prostitution. Madin al-ulya's efforts are not as easy as turning the hand, because in addition to environmental factors, family and parents background factors are be an obstacle. However, the determination of the teachers in Madin Al-Ulya to continue to instill good moral values deserves appreciation, so that more or less those values influence the behavior of the children in that environment, which in turn begins to form good character.